Age in David Almond's Oeuvre A Multi-Method Approach to Studying Age and the Life Course in Children's Literature - Joosen, Vanessa (Children's Literature and Culture, 2024)
In recent decades, age studies has started to emerge as a new approach to study children's literature. This book builds on that scholarship but also significantly extends it by exploring age in various aspects of children's literature: the age of the author, the characters, the writing style, the intended readership and the real reader. Moreover, the authors explore what different theories and methods can be used to study age in children's literature, and what their affordances and limits are. The analyses combine age studies with life writing studies, cognitive narratology, digital humanities, comparative literary studies, reader-response research and media studies. To ensure coherence, the book offers an in-depth exploration of the oeuvre of a single author, David Almond. The aesthetic and thematic richness of Almond's works has been widely recognised. This book adds to the understanding of his oeuvre by offering a multi-faceted analysis of age. In addition to discussing the film adaptation of his best-known novel Skellig, this book also offers analyses of works that have received less attention, such as Counting Stars, Clay and Bone Music. Readers will also get a fuller understanding of Almond as a crosswriter of literature for children, adolescents and adults.